Math, asked by mohitdayalani7523, 1 year ago

If x+y+z=0 then prove that x^3+y^3+z^3=3xyz

Answers

Answered by cosmiccreed
0

Answer:

x^3+y^3+z^3-3xyz=(X+Y+Z)(X^2+Y^2+Z^2-XY-YZ-ZX)

NOW PUT

X+Y+Z=0

RHS BECOMES 0

WE GET

x^3+y^3+z^3=3xyz

Step-by-step explanation:

Answered by Shreyanshijaiswal81
0

x + y + z = 0 =  >  x  + y =  - z \\  =  > (x + y)^{3}  = ( - z )^{3}  \\  =  > x^{3}  + y ^{3}  + 3xy \: (x + y) = ( - z) =  -  {z} \\  =  > x^{3}  + y ^{3}  + 3xy ( - z ) =  -  {z}^{3}  \\  =  > x^{3}  + y ^{3}   -  3xyz  = 3xyz

Hence,(x + y + z) = 0  =  > ( {x}^{3}  {y}^{3}  {z}^{ 3} ) = 3xyz

Similar questions